Pengaruh Good Corporate Governance, Debt default dan Audit Tenure Terhadap Opini Audit Going Concern - Ayu Nurhafizah; Erika Astriani Aprilia (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This research was conducted to analyze the effect of Good Corporate Governance, Debt Default, and Audit Tenure on Audit Opinion Going Concern. The research was conducted on Consumer Non-Cyclicals Sector Companies listed on the Indonesia Stock Exchange in 2020-2024. The methodology used is Logistic Regression because the dependent variables of this study are in the form of dummy variables. Sample selection was carried out using the Purposive Sampling method from secondary data in the form of Financial Statements and found as many as 15 sample companies with a total of 5 years of observations, so that the total sample in this study was 75. Hypothesis testing was carried out using the Eviews series 12 application. The results of the study show that Good Corporate Governance proxied by independent commissioners have an effect on the Audit Opinion of Going Concern, Good Corporate Governance, proxied by managerial ownership have an effect on the Audit Opinion of Going Concern, Debt Default has no effect on the Audit Opinion of Going Concern, and Audit Tenure has no effect on the Audit Opinion of Going Concern.